1996
DOI: 10.1086/118060
|View full text |Cite
|
Sign up to set email alerts
|

Compact Group selection From Redshift Surveys

Abstract: For the first time, we construct a catalog of compact groups selected from a complete, magnitude-limited redshift survey. We select groups with N ≥ 3 members based on projected separation and association in redshift space alone. We evaluate the characteristics of the Redshift Survey Compact Groups (RSCG's). Their physical properties (membership frequency, velocity dispersion, density) are similar to those of the Hickson [ApJ, 255, 382 (1982)] Compact Groups. Hickson's isolation criterion is a strong function o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
174
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(187 citation statements)
references
References 38 publications
12
174
1
Order By: Relevance
“…Therefore, at least some X-rayYluminous, intermediate-redshift groups have central densities comparable to CGs. This result is consistent with the observation that many CGs at low redshift are actually associated with larger galaxy systems (Ramella et al 1994;Barton et al 1996;de Carvalho et al 1997;Ribeiro et al 1998;Tovmassian et al 2006). This is also consistent with the fact that many CGs are luminous in X-rays, although typically with lower luminosities than the groups studied here (Ponman et al 1996).…”
Section: Brightest Group Galaxiessupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, at least some X-rayYluminous, intermediate-redshift groups have central densities comparable to CGs. This result is consistent with the observation that many CGs at low redshift are actually associated with larger galaxy systems (Ramella et al 1994;Barton et al 1996;de Carvalho et al 1997;Ribeiro et al 1998;Tovmassian et al 2006). This is also consistent with the fact that many CGs are luminous in X-rays, although typically with lower luminosities than the groups studied here (Ponman et al 1996).…”
Section: Brightest Group Galaxiessupporting
confidence: 92%
“…As rich systems, our groups do not meet this final isolation criterion; however, a few of them do have several galaxies closely spaced in projection. The galaxies in CGs typically lie within radii of around 100 h À1 70 kpc ( Hickson 1982;Iovino 2002;Iovino et al 2003;Pompei et al 2006;Focardi & Kelm 2002;Barton et al 1996;Allam & Tucker 2000;Lee et al 2004). In column (8) of Table 4, we list the number of galaxies in each group within 100 h À1 70 kpc of the group center and with magnitudes within 3 mag of the BGG.…”
Section: Brightest Group Galaxiesmentioning
confidence: 99%
“…Barton et al (1996) also find a similar space density for nearby CGs, 3:8 ; 10 À5 h 3 Mpc À3 . These two estimates are consistent with each other and were determined using totally different algorithms.…”
Section: The Space Density Of Our Samplesupporting
confidence: 69%
“…In spite of concerns about selection biases in the Hickson catalog (Mamon 1994;Ribeiro et al 1998), it has been shown that several characteristic properties of HCG galaxies are comparable to median galaxy values (e.g., surface brightness and linear or angular diameters, Lee et al 2004, T14). One of our CGs comes from the catalog of Redshift Survey Compact Groups (RSCGs, Barton et al 1996). This RSCG is part of a larger sample selected by Walker et al (2012) to have properties similar to those of HCGs.…”
Section: Sample Selectionmentioning
confidence: 99%